Eksplorasi Faktor-Faktor Online Marketing Yang Memengaruhi Keputusan Konsumen Dalam Belanja Online Pada Naufal Bag Collection - Nia Purwanti; Bambang Irawan; Sriono S (UPT Penerbitan Universitas Jember, 2017)
This study aims to explore online marketing factors that influence purchase decisions and analysis of what factors mostdominant influence. This study uses a quantitative approach. The study population is consumers shop Naufal Bag Collectionever shopped online. Research using purposive sampling size of 125 respondents. Methods of data analysis using factoranalysis. The results showed that the discovered five factors: the process of purchase, price cuts, clarity of information, productexcellence and service excellence that is proven to significantly affect consumer decisions. Naufal product excellence BagCollection is the most dominant factor influencing the consumer's decision to shop online.